Molecular docking-aided identification of small molecule inhibitors targeting β-catenin-TCF4 interaction - Joo-Leng Low; Weina Du; Tenzin Gocha; Gokce Oguz; Xiaoqian Zhang; Ming Wei Chen; Srdan Masirevic; Daniel Guo Rong Yim; Iain Bee Huat Tan; Adaikalavan Ramasamy; Hao Fan; Ramanuj DasGupta (iScience, 2021)
Summary: Here we report a molecular docking-based approach to identify small molecules that can target the β-catenin (β-cat)-TCF4 protein-protein interaction (PPI), a key effector complex for nuclear Wnt signaling activity. Specifically, we developed and optimized a computational model of β-cat using publicly available β-cat protein crystal structures, and existing β-cat-TCF4 interaction inhibitors as the training set. Using our computational model to an in silico screen predicted 27 compounds as good binders to β-cat, of which 3 were identified to be effective against a Wnt-responsive luciferase reporter. In vitro functional validation experiments revealed GB1874 as an inhibitor of the Wnt pathway that targets the β-cat-TCF4 PPI. GB1874 also affected the proliferation and stemness of Wnt-addicted colorectal cancer (CRC) cells in vitro. Encouragingly, GB1874 inhibited the growth of CRC tumor xenografts in vivo, thus demonstrating its potential for further development into therapeutics against Wnt-associated cancer indications.